IMPROVING STUDENTS’ SPEAKING FLUENCY THROUGH THE IMPLEMENTATION OF TRIVIA-BASED ACTIVITY ON UNIVERSITY STUDENTS: IMPROVING STUDENTS’ SPEAKING FLUENCY THROUGH THE IMPLEMENTATION OF TRIVIA-BASED ACTIVITY ON UNIVERSITY STUDENTS - M. Afrizal; Chalil As’ari (Department of English Education, Faculty of Teacher Training and Education, Almuslim University, 2022)
This article describes a classroom action research held in speaking class through the implementation of trivia-based activity to improve the University students’ speaking fluency and improve the classroom situation as well. The method used in the reasearch is collaborative classroom action research which was conducted in two cycles. Each cycle included four stages namely planning, implementing, observing and reflecting. The data that were obtained qualitatively and quantitatively showed that through trivia-based activity could improve: (1) students’ speaking fluency; (2) speaking classroom situation.